STRATEGI PENJUALAN SALES VISIT CORPORATE DAN MICE UNTUK MENINGKATKAN REVENUE DI R HOTEL RANCAMAYA BOGOR - Ade Septiana; Nila Rifai (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Bogor, 2026)
This study examines the influence of Corporate & MICE Sales Visit strategies on increasing Revenue at R Hotel Rancamaya Bogor. Using a quantitative methodology with simple linear regression analysis, this study examines data from January 2023 to December 2024 to determine the relationship between Sales Visit frequency & hotel revenue. The objectives of this study include the following: (1) To determine whether the Sales Visit sales strategy implemented by R Hotel Rancamaya Bogor has an effect on increasing Revenue, (2) To determine whether there is a significant influence on the implementation of the Sales Visit sales strategy with increasing Revenue at R Hotel Rancamaya Bogor, and (3) To determine how much the Sales Visit sales strategy contributes to supporting increased Revenue at R Hotel Rancamaya Bogor. The findings show a significant positive correlation between Sales Visit activities and increased Revenue, where each increase in one Sales Visit unit contributes Rp 13,819,341,904 to hotel revenue. Statistical analysis shows a strong correlation coefficient of 0.558 and a determination coefficient of 31.1%, indicating that Sales Visit strategies explain substantial variation in hotel Revenue. The regression equation Y=-1,556,707,918.253+ 13,819,341,904X confirms the hypothesis that Corporate and MICE Sales Visit strategies contribute significantly to revenue increase with a significance level of 0.005. This study provides empirical evidence supporting the effectiveness of personal selling approaches in the hospitality industry, particularly for the Corporate & MICE segments. This study contributes to the hospitality marketing literature by demonstrating the quantitative impact of relationship marketing strategies on business performance.